Internationalization, Mobility and Englishization in Higher Education Across OECD Countries - Tuğba Elif Toprak (Üniversite Araştırmaları Dergisi)
Although the European Union policies explicitly support the notion of multilingualism, the impact of increasing internationalization on the linguistic landscape of the European higher education system has been dramatic. In the post-Bologna period, the desire of higher education institutions to attract a more skilled and diverse body of students seems to turn English into the medium of instruction of a significant number of higher education institutions based in the continent. Particularly, competitiveness in the academic market that leads to bottom-up and top-down pressures within universities to become more international may have caused many higher education institutions to directly associate internationalization with Englishization. As this situation reinvigorates the status of English as the lingua franca, the present article investigates the links between internationalization, language policies, and Englishization through having a closer look at the OECD international student mobility data. The article also points to several practical and pedagogical considerations involved in implementing language policies in higher education.